Intelligent rehabilitation assistant system to promote the early functional recovery of the elderly patients with femoral neck fracture after hemiarthroplasty (HA): A protocol for a randomized controlled trial. Issue 46 (13th November 2020) - Li, Zige; Lin, Haixiong; Wang, Xiaotong; Huang, Minling; Feng, Junming; Feng, Junjie; Gao, Junyan; Wu, Jingjing; Jiang, Ziwei
Abstract: Background: Femoral neck fracture is a common type of hip fracture, which has a high morbidity and mortality. Surgical treatment is the first choice. However, the functional rehabilitation after operation has not been paid enough attention. In addition, the quality of exercise is difficult to quantify, and the rehabilitation is lack of standards. Therefore, the intelligent rehabilitation assistant system which could record exercise details, might be used to evaluate the quality and adherence to the prescribed exercise to this fragile group of patients has great relevance, so as to provide new ideas for postoperative rehabilitation of hip fracture. Methods: This is an opening, prospective, double-dummy RCT. Fifty femoral neck fractures patients, older than 65 years and are about to hospitalize for HA, will be invited to study. The sample will be divided into monitoring group and control group randomly at a 1:1 ratio. The prescribed exercises need to be done continuously for 2 weeks. The monitoring group needs additional use intelligent rehabilitation assistant system. Each subject will receive a total of 4 follow-up visits at the designated time (2 weeks, 4 weeks, 12 weeks, and 24 weeks). The following factors will be talked as dependent variables: Hip function, measured by Harris Hip Score (HHS); self care ability, based on the Activity of Daily Living Score (ADL) and The timed "up & go" text; pain, using Visual analog scale (VAS); Postoperative complications and 6-month mortality. Each subject will receive a total of 4 follow-up visits at the designated time, and the findings will be analyzed statistically considering a 5% significance level ( P  < .05). Discussion: Exercise under monitor may improve patients compliance and exercise quality, and accelerate the rehabilitation process. This protocol reported in accordance with the CONSORT 2010 checklist and SPIRIT 2013 Checklist. Trial registration: The trial is registered at Chinese Clinical Trials Registry (ChiCTR2000033213, May 24, 2020).